Changes in the Syndesmotic Reduction After Syndesmotic Suture-Button Fixation for Ankle Malleolar Fractures: 1-Year Longitudinal Evaluations Using Computed Tomography. (October 2021) - Kimura, Seiji; Yamaguchi, Satoshi; Ono, Yoshimasa; Watanabe, Shotaro; Akagi, Ryuichiro; Sasho, Takahisa; Ohtori, Seiji
Background: Evaluation over time is important in assessing the reduction of the syndesmosis after suture-button fixation for ankle malleolar fractures. The purposes of this study were to evaluate time-dependent change in the syndesmotic reduction immediately after suture-button fixation for ankle malleolus fractures and 1 year after surgery using computed tomography, and to investigate the reliability of the measurement values to evaluate the reduction of syndesmosis. Methods: We assessed 28 patients who underwent suture-button fixation for ankle fractures. Syndesmotic reduction was assessed within 2 weeks of the fracture surgery and 1 year after surgery using axial computer tomographic images. Side-to-side differences in the anterior, central, and posterior tibiofibular distances, anteroposterior fibular translation, fibular rotation, and syndesmosis area were measured. Results: The mean anterior tibiofibular distance and anteroposterior fibular translation were 1.8 mm and 1.5 mm, respectively, after syndesmotic fixation. They decreased to 1.2 mm and 0.6 mm, respectively, at 1 year after surgery ( P = .03 and P = .01, respectively). The other measurement values did not change over time. The minimum detectable change in the distance of measurements was 1 mm or less. Conclusion: The anterior tibiofibular distance and anteroposterior fibular translation had decreased 1 year after fixation in ankle malleolar fractures with syndesmotic suture button. Even if the fibula is posteriorly malreduced by the time computed tomography is performed immediately after surgery, the fibula may return to a good position 1 year after surgery. Level of Evidence: Level IV, case series.